2015
DOI: 10.1186/s40792-015-0107-4
|View full text |Cite
|
Sign up to set email alerts
|

A rare combination of pheochromocytoma and gastrointestinal stromal tumour in a patient with neurofibromatosis 1 syndrome—a case report

Abstract: Neurofibromatosis 1 is a rare inherited autosomal dominant syndrome. It comprises 90 % of neurofibromatosis cases. These patients may develop various types of tumours in early age, especially multiple neurofibromas with a high risk of developing malignant peripheral nerve sheath tumours. Other tumours can also develop like pheochromocytoma, optic nerve and brain stem gliomas, carcinoids and rarely gastrointestinal stromal tumours. A combination of pheochromocytoma and gastrointestinal stromal tumour is very ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…One of the authors of this article has reported a case with a rare combination of ileal GIST and pheochromocytoma in a neurofibromatosis 1patient. 2 There is an increasing number of literature reports on synchronous occurrence of gastrointestinal stromal tumors and another malignancy of distinct etiology and evolution. 3 GIST arises from interstitial cells of Cajal and adenocarcinoma is an epithelial malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…One of the authors of this article has reported a case with a rare combination of ileal GIST and pheochromocytoma in a neurofibromatosis 1patient. 2 There is an increasing number of literature reports on synchronous occurrence of gastrointestinal stromal tumors and another malignancy of distinct etiology and evolution. 3 GIST arises from interstitial cells of Cajal and adenocarcinoma is an epithelial malignancy.…”
Section: Discussionmentioning
confidence: 99%